2015
DOI: 10.3892/ol.2015.3391
|View full text |Cite
|
Sign up to set email alerts
|

Guggulsterone inhibits human cholangiocarcinoma Sk-ChA-1 and Mz-ChA-1 cell growth by inducing caspase-dependent apoptosis and downregulation of survivin and Bcl-2 expression

Abstract: Abstract. Guggulsterone has recently been reported to demonstrate anti-tumor effects in a variety of cancers. The present study aims to investigate the biological roles and underlying mechanism of the action of guggulsterone in cholangiocarcinoma. The immortalized human cholangiocarcinoma Sk-ChA-1 and Mz-ChA-1 cell lines were treated with various concentrations of the trans isomer of guggulsterone, Z-guggulsterone. Cellular proliferation was determined using the XTT assay. The apoptotic status of cholangiocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…Treatment with 20mM DCA promotes robust cell death marked by extensive mitochondrial release of cytochrome c, indicative of apoptotic cell death ( S1 Fig ). Consistent with this immunofluorescent data, the addition of the pan-caspase inhibitor Z-VAD-FMK attenuated DCA cytotoxicity [ 38 , 39 ] ( S1 Fig ).…”
Section: Resultssupporting
confidence: 72%
“…Treatment with 20mM DCA promotes robust cell death marked by extensive mitochondrial release of cytochrome c, indicative of apoptotic cell death ( S1 Fig ). Consistent with this immunofluorescent data, the addition of the pan-caspase inhibitor Z-VAD-FMK attenuated DCA cytotoxicity [ 38 , 39 ] ( S1 Fig ).…”
Section: Resultssupporting
confidence: 72%
“…Previous studies have suggested survivin is upregulated in CCA tissues, and inhibition of survivin promoted cell apoptosis [10,11].…”
Section: Introductionmentioning
confidence: 91%
“…Alternatively, IGFBP-2 played an important role in cell proliferation, invasion, angiogenesis and apoptosis [32]. Simultaneously, Survivin as an important member of IAP, which were considered to be a regulator of apoptosis related proteins and prevention of apoptosis, and it was strongly expressed in CCA [33][34][35]. TNF-β also was identi ed as a key mediator between apoptosis and cancer cell progression [36].…”
Section: Discussionmentioning
confidence: 99%